Cloxacillin control of experimental arthritis induced by SEC+ Staphylococcus aureus is associated with downmodulation of local and systemic cytokines - Colavite, Priscila Maria [UNESP]; Ishikawa, Larissa Lumi Watanabe [UNESP]; Zorzella-Pezavento, Sofia Fernanda Gonçalves [UNESP]; Oliveira, Larissa Ragozo Cardoso de [UNESP]; França, Thaís Graziela Donegá [UNESP]; da Rosa, Larissa Camargo [UNESP]; Chiuso-Minicucci, Fernanda [UNESP]; Vieira, Andreia Espíndola; Francisconi, Carolina Fávaro; da Cunha, Maria de Lourdes Ribeiro de Souza [UNESP]; Garlet, Gustavo Pompermaier; Sartori, Alexandrina [UNESP] (Hindawi, 2016)
Staphylococcus aureus is the most common agent of septic arthritis (SA) that is a severe, rapidly progressive and erosive disease. In this work we investigated the clinical, histopathological and immunological characteristics of the SA triggered by an enterotoxin C producer S. aureus strain. The effect of a β-lactamic antibiotic over disease evolution and cytokine production was also evaluated. After confirmation that ATCC 19095 SEC+ strain preserved its ability to produce enterotoxin C, this bacteria was used to infect C57BL/6 male mice. Body weight, clinical score and disease prevalence were daily evaluated during 14 days. Cytokine production by splenocytes, cytokine mRNA expression in arthritic lesions, transcription factors mRNA expression in inguinal lymph nodes and histopathological analysis were performed 7 and 14 days after infection. ATCC 19095 SEC+ strain caused a severe arthritis characterized by weight loss, high clinical scores and a 100% disease prevalence. Histopathological analysis revealed inflammation, pannus formation and bone erosion. Arthritis aggravation was associated with elevated production of pro-inflammatory cytokines, higher local mRNA expression of these cytokines and also higher mRNA expression of T-bet, ROR-γ and GATA-3. Disease control by cloxacillin was associated with decreased production of pro-inflammatory cytokines but not of IL-10. These findings indicate that the ATCC 19095 SEC+ strain is able to initiate a severe septic arthritis in mice associated with elevated cytokine production that can be, however, controlled by cloxacillin.
Keywords: cloxacillin; cytokines; enterotoxin C; septic arthritis; Staphylococcus aureus